Development of learning trajectory of perimeter and area of squares and rectangles through various tasks - Labibah Kurniawati; Mohammad Faizal Amir (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2022)
Learning trajectory on the topic of plane figures (i.e., perimeter and area of squares and rectangles) is necessary for elementary students to facilitate meaningful learning and predict their learning progress. This study aims to develop a learning trajectory through various tasks for the perimeter and area of squares and rectangles that can help students develop understanding and construct mathematical concepts. Study participants were fourth grade elementary students. The method used was design research, which has three stages: preparing for the experiment, teaching, and retrospective analysis. This study used data collection instruments in worksheets, observation sheets, interview guidelines, and field notes. Research results obtained included a learning trajectory that contains adequate learning activities to facilitate learning for elementary students on the perimeter and area of squares and rectangles. Adequate learning trajectory is obtained in hypothetical learning trajectory (HLT) 2, which was previously revised from HLT 1. Learning trajectory developed through a variety of tasks can significantly construct and facilitate elementary students’ knowledge to learn the concepts of perimeter and area of squares and rectangles.